The anti-mass and unruly urban sociability. Social distancing as a clarification of publicness - Nicholas DeMaria Harney (lo Squaderno, 2022)
In 1900 the Irish anthropologist and linguist George Abraham Grierson described the Pulayar of Travancore and the relationship between Braham and Sudra in South India, which was based on ‘silent trade’ between these two unequal parties: “If he wishes to make a purchase, he places his money on a stone, and retires to the appointed distance. The merchant or seller comes, takes up the money, and lays down whatever quantity of goods he chooses to give for the sum received” (Grierson 1903: 64).